Scientific perspective on rukyatul hilal: A case study of assalam kartasura sukoharjo observatory - Riky Supratama; Elisa Putri Kholifah; Amartya Nadienil Millah; Warda Helwiyah (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
In essence, rukyat is looking deeply to see whether the moon has undergone changes to indicate the change of the moon or not. With the advancement of the times, observations no longer only use manual binoculars but are supported by various adequate equipment, making it very easy to carry out observations. . Therefore, it is important for humanity to understand what an observatory is and its uses. This research uses qualitative methods supported by documentation and direct field research at the Assalam observatory in Sukoharjo, Central Java. The results of this research are the contribution of the Assalam Observatory in the implementation of rukyatul hilal in Indonesia. The Assalam Observatory is also the Secretary General of JOPI (Indonesian Planetarium Observatory Network) so its involvement in rukyatul hilal is beyond doubt. So far, the results of observations at the Assalam observatory are at 7-8 degrees every month.